2020
DOI: 10.1016/j.jinf.2020.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy in severe COVID-19: A retrospective study of short-term treatment efficacy and side effects

Abstract: Comparing hospitalised, community and staff COVID-19 infection rates during the early phase of the evolving COVID-19 epidemicDear Editor,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 7 publications
1
62
0
1
Order By: Relevance
“…MSC-based therapy protocols to treat COVID-19 have been directed mainly to patients with moderate and severe clinical presentations [9][10][11][12][13][14][15][16][17][18]. Few numbers of studies included critically ill patients with COVID-19 under invasive mechanical ventilation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…MSC-based therapy protocols to treat COVID-19 have been directed mainly to patients with moderate and severe clinical presentations [9][10][11][12][13][14][15][16][17][18]. Few numbers of studies included critically ill patients with COVID-19 under invasive mechanical ventilation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest an increase in peripheral blood regulatory T cells and dendritic cells in patients with more severe COVID-19, and reduction in circulating IL-10 and TNF-α levels, provide evidence of immunomodulation [133]. Chen et al, 2020, reported a retrospective review of 25 patients who received MSC therapy (between 1 and 3 infusions of 1 × 10 6 cells/kg) for COVID-19 pneumonia [134]. Data reported is extremely limited, with no detail of baseline physiological status or COVID-19 severity.…”
Section: Mscs In Covid-19 Trials and Reports (Summary Table 4)mentioning
confidence: 99%
“…In this context, MSC-based therapy would be plausible, because they are easily available and expanded from allogeneic tissue source, they may be previously cryopreserved and available “off the shelf” and easily intravenously infused. The remarkable immunomodulatory and regenerative abilities of MSCs may be effective for attenuating the cytokine storm and preventing progression to ARDS and multiple organ failure in severe COVID-19 patients [ 5 , 103 , 105 , 123 – 125 , 127 , 129 ]. In addition, intravenously infused MSCs become trapped in the lung.…”
Section: Future Directions Of Msc-based Therapies For Covid-19 and Otmentioning
confidence: 99%